A Management Science Approach to Contingency Models of Organizational Structure - Lee, Sang M.; Luthans, Fred; Olson, David L. (Academy of Management Journal, 1982)
This study demonstrates the applicability of a quantitative modeling approach, specifically goal programming, in operationalizing the relationship between environmental variables and specific organizational structural variables for optimal goal attainment. A goal programming model is developed to analyze and determine the optimal relationships for goal attainment.